2020
DOI: 10.1111/tri.13636
|View full text |Cite
|
Sign up to set email alerts
|

Are the outcomes of Japanese pancreas transplantation utilizing extended‐criteria donors acceptable? A propensity score matching analysis for donors <50 or ≥50 years old

Abstract: Summary In Japan, about 30% of pancreatic transplant donors are ≥50 years old, making them “extended‐criteria donors (ECDs).” We analyzed 361 cases of transplantation involving donors from the Japanese pancreas transplantation registry to evaluate the acceptability of ECDs. The patient survival rates at 1, 5, and 10 years after transplantation were 96.6%, 94.9%, and 88.3%, respectively. The survival rates of pancreas and kidney grafts at 1, 5, and 10 years were 85.3%, 74.8%, and 70.6%, and 94.2%, 90.9%, and 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…The cutoff value for donor age was set to 50 years, which is often discussed as a marginal donor criterion for pancreas transplantation with graft survival as an outcome. [11][12][13]15 It was revealed that pancreatic grafts from donors 50 years or older were shown to have a poorer endocrine function in comparison with those from younger donors in this study. In addition to having a negative impact on pancreatic graft survival, 14 donation from older donors and donors who have died of CVA is associated with the possibility of atherosclerosis, which may result in reduced insulin secretion ability.…”
Section: Discussionmentioning
confidence: 94%
“…The cutoff value for donor age was set to 50 years, which is often discussed as a marginal donor criterion for pancreas transplantation with graft survival as an outcome. [11][12][13]15 It was revealed that pancreatic grafts from donors 50 years or older were shown to have a poorer endocrine function in comparison with those from younger donors in this study. In addition to having a negative impact on pancreatic graft survival, 14 donation from older donors and donors who have died of CVA is associated with the possibility of atherosclerosis, which may result in reduced insulin secretion ability.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, due to the pooling of the various causes of pancreas graft loss, the statistical analyses may have overestimated the significance of certain factors. Ito et al demonstrated that no factors significantly influenced pancreatic graft survival in a multivariate analysis of post-PTx outcomes based on the Japanese database 19 . If they had performed the analysis based on cause-specific subgroups, their results would have been similar to those reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…1-, 5-и 10-летняя выживаемость реципиентов, согласно данным трансплантационных центров, колеблется в пределах от 82 до 100%, от 81 до 95% и от 67 до 83% соответственно; почечного трансплантата -от 80 до 98%, от 63 до 94% и от 57 до 81% соответственно; ТПЖ -от 71 до 95%, от 59 до 94%, от 53 до 71% соответственно [7][8][9][10][11][12][13][14][15][16]…”
Section: Discussionunclassified